Palaeobathymetric reconstruction of the Africa-Antarctic conjugate margin - Castelino, Jude A.; Jokat, Wilfried (ISAES - 2015, 2015)
An extensive database of geophysical data in the Riiser-Larsen Sea and Mozambique Basin conjugate margins indicates a dynamic evolution that was actively influenced by different events. However, analyses of individual datasets are not sufficient to reconstruct the complete structural evolution of the rifted margins during Gondwana break-up and thereon. We use crustal age models and chronology of interpreted horizons from extensive seismic datasets in the Riiser-Larsen Sea and off Mozambique to create the palaeobathymetric reconstruction of the conjugate margins. We also incorporate the effects of different models for sediment decompaction, thermal subsidence and lithospheric flexure from sediment loading and sea level variation into our calculations. The geodynamics of the two passive margins is reconstructed on a 0.5° x 0.5° grid resolution. Plate kinematic model of Antarctic plate with respect to Africa controls palaeogeography of the break-up. The model shows the initial period of common phases of the geodynamic evolution of the two margins. The results provide new boundary conditions for palaeoenvironment settings, palaeoceanographic models and sediment deposition architecture in the Africa-Antarctic corridor.